Social Emotional Development Program through an Integrative Holistic Approach for Early Autistic Children in Inclusive Kindergarten - Anggawati Imanniyah; Budiyanto Budiyanto; I Ketut Budayasa (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2018)
Not every child successfully passes the task of social emotional development at an early age so that various obstacles can occur, especially in children with autism. To overcome this problem, a program is needed to help achieve the task of developing the social emotional development of autistic children through an integrative holistic approach. The purpose is to produce a prototype of social emotional development program through an integrative holistic approach that meets valid, practical and effective criteria. Program development in this study uses the Thiagarajan‘s Four-D development model. The result is a prototype program in the form of a book and accompanied by implementation guidelines. The results show that the prototype is valid, feasible, and effective.. Thus, it can be concluded that a social emotional development program through integrative holistic approach is proper to be used.